Exploration of Antimicrobial Ingredients in Psoralea corylifolia L. Seed and Related Mechanism against Methicillin-Resistant Staphylococcus aureus - Liqiong Sun; Zhijuan Tang; Minxin Wang; Jun Shi; Yajuan Lin; Tiefeng Sun; Zhilu Zou; Zebin Weng (Molecules, 2022)
With the abuse of antibiotics, bacterial antibiotic resistance is becoming a major public healthcare issue. Natural plants, especially traditional Chinese herbal medicines, which have antibacterial activity, are important sources for discovering potential bacteriostatic agents. This study aimed to develop a fast and reliable method for screening out antimicrobial compounds targeting the MRSA membrane from Psoralea corylifolia Linn. seed. A UPLC-MS/MS method was applied to identify the prenylated flavonoids in major fractions from the extracts of Psoralea corylifolia Linn. seed. The broth microdilution method was used to determine the minimum inhibitory concentrations (MICs) of different fractions and compounds. The morphological and ultrastructural changes of MRSA were determined by scanning electron microscopy (SEM). The membrane-targeting mechanism of the active ingredients was explored by membrane integrity assays, membrane fluidity assays, membrane potential assays, ATP, and ROS determination. We identified eight prenylated flavonoids in Psoralea corylifolia Linn. seed. The antibacterial activity and mechanism studies showed that this type of compound has a unique destructive effect on MRSA cell membranes and does not result in drug resistance. The results revealed that prenylated flavonoids in Psoralea corylifolia Linn. seeds are promising candidates for the development of novel antibiotic agents to combat MRSA-associated infections.